Foliar nutrient application improves sugarcane bioenergy production by boosting photosynthetic enzyme activity and the antioxidant system - Crusciol, Carlos Alexandre Costa [UNESP]; de Almeida Prado Filho, Anibal Pacheco [UNESP]; de Morais Hervatin, Cleber [UNESP]; Momesso, Letusa; Jacomassi, Lucas Moraes [UNESP]; Pacola, Marcela [UNESP] (Wiley, 2025)
Abstract Sugarcane ( Saccharum spp. L.) is a globally important crop, and foliar fertilization can enhance plant growth, yield, and stress tolerance. However, the use of multi‐nutrient complexes remains underexplored. Here, we investigated the effect of two multi‐nutrient foliar fertilizer applications at vegetative stage (N, K, S, B, Cu, Mn, Mo and Zn) and at maturation stage (P, K, Mg, S and B) in 13 field experiments in the early, mid‐late, and late sugarcane harvest seasons. Four treatments were compared: (i) no application of multi‐nutrient foliar fertilizer (control), (ii) application at the vegetative stage of sugarcane (V), (iii) application at the maturation stage (M), and (iv) application at both the vegetative and maturation stages (VMs). Application resulted in significant gains in all biometric parameters, sugar yield, and theoretically recoverable sugars; the largest increases occurred in VM. Bagasse, straw, and energy production followed the pattern of biometric parameters and increased by averages of 7.9%, 9.7%, and 9.7% compared to the control. In early harvest sugarcane, phosphoenolpyruvate carboxylase, ribulose‐1,5‐bisphosphate carboxylase‐oxygenase, superoxide dismutase, catalase, ascorbate peroxidase, and peroxidase activities and proline content were enhanced in M and VM, whereas hydrogen peroxide (H 2 O 2 ) and malondialdehyde contents decreased in these treatments. In summary, multi‐nutrient foliar fertilization at the VMs enhanced sugarcane growth, yield, energy production, and quality across all harvest seasons while improving photosynthetic and antioxidant enzyme activities. The results demonstrate that tailoring multi‐nutrient foliar fertilizer application to the specific physiological and nutritional demands of each phenological stage can promote sugarcane development by reducing the production of stress‐related molecules and enhancing carbon assimilation. Core Ideas Multi‐nutrient foliar fertilization can boost biomass production. Foliar application supplies the plant's metabolic demand for reactive oxygen species (ROS) scavenging. Application increases stalk and sugar yields by increasing photosynthetic enzyme activity. Application increases energy production potential by increasing biomass. Plain Language Summary Oxidative stress limits plant development and leads to undesirable morphological and physiological changes, most notably overproduction of reactive oxygen species. Foliar supplements containing specific nutrients can increase plant metabolism, stalk and sugar yields, and the quality of the extracted juice. Therefore, this study aims to evaluate the influence of a single foliar application and/or two sequential applications at final stages (vegetative and maturation) of a multi‐nutrient complex in sugarcane at three times of the year (early, mid‐late, and late sugarcane seasons) to increase productivity and crop quality. Multi‐nutrient fertilization had a relevant effect on plant growth and yield in early, middle, and late sugarcane seasons, with gains in plant height, diameter, and stalk yield. Also increased quality parameters as sucrose content, TRS, and sugar yield. In addition, foliar fertilization of nutrients benefited energy parameters of bagasse and energy production.